Necobelac supporting open access, a path to open science (2011)
On the occasion of the International Open Access week, a global event now in its 5th year, promoting Open Access (OA) as a new norm in scholarship and research, we, the NECOBELAC (Network of collaboration between Europe and Latin American Caribbean (LAC) countries to spread know-how in scientific writing and provide the best tools to exploit open access information for the safeguard of public health) project partners, wish to stimulate the scientific community to take action and make their work open access to disseminate free health information worldwide. NECOBELAC is one of the many initiatives in support of OA; it is a project involving European and Latin American and Caribbean institutions to promote the diffusion of health information through a training programme, addressed to different stakeholders, aiming to improve scientific writing skills and create awareness on the OA publishing models (www.necobelac.eu).